2022
DOI: 10.3390/en15010281
|View full text |Cite
|
Sign up to set email alerts
|

Financing Efficiency Evaluation and Influencing Factors of Hydrogen Energy Listed Enterprises in China

Abstract: Existing studies of financing efficiency concentrate on capital structure and a single external environment or internal management characteristic. Few of the studies include the internal and external financing environments at the same time for hydrogen energy industry financing efficiency. This paper used the data envelopment analysis (DEA) model and the Malmquist index to measure the financing efficiency of 70 hydrogen energy listed enterprises in China from 2014 to 2020 from both static and dynamic perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…In recent years, scholars have found that the process of enterprise digital transformation is affected by many factors, such as the awareness of digital transformation (Hanelt et al, 2021); Technological transition (Rohracher, 2001); Infrastructure construction (Chang and Kendall, 2011); Management change (Jilte et al, 2021); Internal factors of enterprises (Chi et al, 2022); Policy promotion (Vu and Hartley, 2022); Enterprise cooperation (Zhang et al, 2022); Influence of external factors such as government guidance (Llopis-Albert et al, 2021); Environmental factors (Feroz et al, 2021;Chen and Tian, 2022). In the context of China, the digital transformation of satellite communication enterprises needs to be considered comprehensively by combining their own characteristics and integrating various factors (Giua et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, scholars have found that the process of enterprise digital transformation is affected by many factors, such as the awareness of digital transformation (Hanelt et al, 2021); Technological transition (Rohracher, 2001); Infrastructure construction (Chang and Kendall, 2011); Management change (Jilte et al, 2021); Internal factors of enterprises (Chi et al, 2022); Policy promotion (Vu and Hartley, 2022); Enterprise cooperation (Zhang et al, 2022); Influence of external factors such as government guidance (Llopis-Albert et al, 2021); Environmental factors (Feroz et al, 2021;Chen and Tian, 2022). In the context of China, the digital transformation of satellite communication enterprises needs to be considered comprehensively by combining their own characteristics and integrating various factors (Giua et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…What we discuss is the calculation of financing efficiency of a low-carbon supply chain, focusing on low carbon, which is somewhat different from the indicators selected in the previous literature. Based on the studies of domestic and foreign scholars [3,58,60], we selected the traditional indicators for measuring financing efficiencies, such as total enterprise assets, asset-liability ratio, and commercial credit. The financial behavior scale of the low-carbon supply chain is innovatively designed and integrated into the measurement index system.…”
Section: Input Indicatorsmentioning
confidence: 99%
“…Achieving the dual-carbon target ("carbon peaking and carbon neutralization") is the common consensus of all countries in the world for high-quality development and the inevitable choice for China's ecological civilization construction [1][2][3]. However, China's total CO 2 emissions rank first in the world, accounting for 28% of the global CO 2 emissions in 2019 [4].…”
Section: Introductionmentioning
confidence: 99%
“…e digital process is the process of storing and developing data through the new generation of information technology. e digital economy is the new economy form of digital knowledge and information as new production activities, digital technology tools, and information networks [11]. e digital process is shown in Figure 2.…”
Section: Digital Transformation Of Enterprisesmentioning
confidence: 99%